A profile study of the students of the University of the Philippines at Clark Air Base - Bacani, Edna Navarro 1947- (s.n.], 1973)
This study determined the characteristics of the students enrolled at the University of the Philippines at Clark Air Base during the first trimester of school year 1972-1973. This could serve as information for the guidance services in the said college.